2017
DOI: 10.5614/api.v42i2.5603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drug-Related Problems on Beta Lactam Antibiotics Used for Pediatric at a Secondary-Care Hospital in Cimahi

Abstract: WHO estimated that >50% of medicines are used inappropriately. One that posess highest risk due to inappropriate use is beta-lactam antibiotic, espescially in pediatric patient since the organ function in pediatric patient has not fully developed as in adult yet. This cross-sectional study was performed to identify drug-related problems (DRPs) occurred during beta-lactam therapy in pediatric hospitalized in a secondary-care hospital in Cimahi. A predetermined medication-use criteria based on the current lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Underdose is more common than overdose. Zazuli et al 17 reported that the highest incidence of DRP is a mismatch of therapeutic doses where 30% of patients with diarrhea received doses of antibiotics that are smaller than those that should be recommended for therapy. A study concerning the use of antibiotics in pediatric patients in District General Hospital, Semarang reported that among 28% of patients experiencing DRPs in the form of underdose.…”
Section: Underdosementioning
confidence: 99%
See 2 more Smart Citations
“…Underdose is more common than overdose. Zazuli et al 17 reported that the highest incidence of DRP is a mismatch of therapeutic doses where 30% of patients with diarrhea received doses of antibiotics that are smaller than those that should be recommended for therapy. A study concerning the use of antibiotics in pediatric patients in District General Hospital, Semarang reported that among 28% of patients experiencing DRPs in the form of underdose.…”
Section: Underdosementioning
confidence: 99%
“…21 Whereas a study in in a Secondary Care Hospital in Cimahi, West Java reported that the antibiotic therapy without indication is 27.73%. 17 Majority antibiotics were empirically prescribed without microbial culture and antibiotic sensitivity test. The antibiotics were prescribed mostly for fever or symptoms associated with the upper respiratory tract infections which commonly caused by viral infections.…”
Section: Therapy Without Indicationmentioning
confidence: 99%
See 1 more Smart Citation